Efficacy of trastuzumab emtansine (T-DM1) and lapatinib after dual HER2 inhibition with trastuzumab and pertuzumab in patient with metastatic breast cancer: Retrospective data from a French multicenter real-life cohort - Moinard-Butot, Fabien; Saint-Martin, Caroline; Pflumio, Carole; Carton, Matthieu; Jacot, William; Cottu, Paul-Henri; Diéras, Véronique; Dalenc, Florence; Goncalves, Anthony; Debled, Marc; Patsouris, Anne; Mouret-Reynier, Marie-Ange; et al. (Breast (Edinburgh), 2022)
Trastuzumab-emtansine (T-DM1), as well as lapatinib plus capecitabine were proven effective in two Phase III studies, following first-line trastuzumab plus a taxane. The introduction of dual HER2 blockade by trastuzumab and pertuzumab as first-line has positioned T-DM1 into second-line, and lapatinib plus capecitabine beyond, without formal evaluation of these strategies. ESME Data Platform (NCT03275311) included individual data from all patients aged ≥18 years, in whom first-line treatment for metastatic breast cancer (MBC) was initiated between January 1, 2008 and December 31, 2016 in one of the 18 French Comprehensive Cancer Centers. The efficacy of T-DM1 and lapatinib plus capecitabine combination, following double blockade associating trastuzumab and pertuzumab were evaluated in this national real-life database. Eligibility criteria were: female, MBC, HER2+ tumor, first-line taxane-based chemotherapy and dual HER2-blockage by trastuzumab plus pertuzumab. Cohort A received second-line T-DM1, and Cohort B second-line T-DM1 and third or fourth-line lapatinib plus capecitabine. Cohort A comprised 233 patients, and Cohort B 47 patients. Median progression-free survival (PFS) was 7.1 months in Cohort A and 4.6 months in Cohort B. Median overall survival were 36.7 months and 12.9 months, respectively. PFS was significantly dependent on the preceding treatment line's duration. In cohort A, HER2 expression status was a significant predictive factor of PFS. First-line trastuzumab plus pertuzumab do not markedly diminish T-DM1's efficacy in second-line. Similarly, sequential treatment with trastuzumab plus pertuzumab then T-DM1 does not noticeably modify the efficacy of lapatinib plus capecitabine. •French real-life cohort.•Dual blockade HER2 does not markedly diminish T-DM1's activity in second-line and lapatinib's activity in third or fourth line.•The second-line (T-DM1) PFS was significantly longer when the first-line treatment with trastuzumab plus pertuzumab was ≥12 months.